Pemanfaatan Aplikasi Smartphone Android dalam Pengambilan Data Cagar Budaya - Helmi Yanuar Dwi Prasetyo; Komang Ayu Suwindiatrini (Tumotowa, 2020)
A Smartphone is a gadget that has the ability to resemble a computer. Smartphones are equipped with hardware and internet networks, so they can be used for various purposes in an era of sophistication. The most commonly used smartphones are those based on the Android Operating System (OS), which is also a competitor of Windows Mobile and iOS. As the most OS with the largest users in the world, it is reasonable that many developers aim at Android and develop applications for the collection of Cultural Heritage data. Often, during the Cultural Heritage data collection activities, the field team is constrained by several tools such as GPS, cameras, and measuring instruments, especially for the general public. But with the advanced features available on smartphones, all of that can be done quickly and accurately in one device. This is very helpful for agencies and the public in collecting data or registering Cultural Heritage. Furthermore, this article provides examples of several applications provided by developers on Android-based smartphones, which can be used to collect Cultural Heritage data. In addition, this also aims to find out which applications can support accurate data collection features, and are available for free on Play Store services provided by Android.